La inversión japonesa en Perú: estrategia en Latinoamérica y plataformas de inversión - Kamiya, Marco (1998)
Against the Peruvians expectations, in the 90s there has not been a massive Japanese private investment. In this work, the author explains this matter, and shows that Japanese Foreign Direct lnvestment in Peru was substantial in his beginnings, in the 60s and 70s, and might be entering lo a future stage of strengthening, depending on the policies applied by Peru and the Japanese strategy centered on the platforms of investment and export. For a promotion policy, is highlighted the necessity to observe the singular conception of flying geese-pattern' model, the business conglomerates system, Keiretsu, and the global commercialization companies, Sogo-Shosha.